Oncogenic and teratogenic effects of Trp53Y217C, an inflammation-prone mouse model of the human hotspot mutant TP53Y220C - Jaber, Sara; Eldawra, Eliana; Rakotopare, Jeanne; Simeonova, Iva; Lejour, Vincent; Gabriel, Marc; Cañeque, Tatiana; Volochtchouk, Vitalina; Licaj, Monika; Fajac, Anne; Rodriguez, Raphaël; Morillon, Antonin; et al. (eLife, 2025)
Missense ‘hotspot’ mutations localized in six p53 codons account for 20% of TP53 mutations in human cancers. Hotspot p53 mutants have lost the tumor suppressive functions of the wildtype protein, but whether and how they may gain additional functions promoting tumorigenesis remain controversial. Here, we generated Trp53Y217C, a mouse model of the human hotspot mutant TP53Y220C. DNA damage responses were lost in Trp53Y217C/Y217C (Trp53YC/YC) cells, and Trp53YC/YC fibroblasts exhibited increased chromosome instability compared to Trp53-/- cells. Furthermore, Trp53YC/YC male mice died earlier than Trp53-/- males, with more aggressive thymic lymphomas. This correlated with an increased expression of inflammation-related genes in Trp53YC/YC thymic cells compared to Trp53-/- cells. Surprisingly, we recovered only one Trp53YC/YC female for 22 Trp53YC/YC males at weaning, a skewed distribution explained by a high frequency of Trp53YC/YC female embryos with exencephaly and the death of most Trp53YC/YC female neonates. Strikingly, however, when we treated pregnant females with the anti-inflammatory drug supformin (LCC-12), we observed a fivefold increase in the proportion of viable Trp53YC/YC weaned females in their progeny. Together, these data suggest that the p53Y217C mutation not only abrogates wildtype p53 functions but also promotes inflammation, with oncogenic effects in males and teratogenic effects in females.
Keywords: hotspot p53 mutant; p53Y220C; gain of function; exencephaly; inflammation; sex-specific effects